Adapting the Nigerian Architectural Educational Schools Curriculum Towards Global Competitiveness - Ilesanmi, Oluropo Stephen; Ojo, Emmanuel Temitope; Kolade, Olaiya Olusegun; Folorunso, Sefunmi; Arawomo, Oladapo Augustine (CV. Gio Architect, 2024)
Globalization refers to the increasing connectedness of nations and peoples around the world through trade, investment, travel, popular culture and other forms of interaction. Globalization through information technology has brought so many openings that are breaking down boundaries hitherto existing in the practice of architecture. To enhance his place in the global market, the Nigerian architect needs to improve his skills on information communication technology (ICT). This paper examines how ICT enhances the global relevance of the Nigerian architect. It also examines the effectiveness and deficiencies of the curriculum in the Nigeria Schools of architecture. The paper therefore advocates a review of the curriculum in the Nigerian Schools of architecture to position the Nigerian architect for global competitiveness.